Islamic Law And Environmental Sustainability: Ri'ayah Al-Bi'ah's Analysis of Fast-Fashion Culture In Indonesia (Program Studi Hukum Keluarga Islam, 2025)
Environmental pollution caused by the fast-fashion industry is an irrefutable fact. The fashion market in Indonesia is contributing to the waste generated by clothing production. Meanwhile, the majority of studies related to clothing from the perspective of Islamic law only focus on the issues of aurat, halal, and haram, and mostly ignore the environmental aspects. This article aims to analyze the fast-fashion phenomenon in Indonesia, from the production process to post-consumer, using the ri'ayah al-bi'ah framework. This research uses a qualitative method by collecting data from literature related to fast-fashion, production waste, and the principle of ri'ayah al-bi'ah. The results of this study show that, in Islam, preserving nature and the environment is an obligation that comes from sharia. Consumers of clothing, manufacturers in the fast-fashion production chain, and the government have important roles in protecting the environment. The study identifies two models of preserving nature based on the concept of ri'ayah al-bi'ah: preserving from the positive aspect (sustainability and preservation) and the negative aspect (preventing damage and destruction). This article finds that fashion production-consumer practices are not yet in accordance with the principles of environmental preservation taught by Islam. The implication of this study is the need for active roles from consumers, producers, and the government in protecting nature, especially in the context of the fast-fashion market in Indonesia. The results of this study offer insight into the obligation to protect the environment in Islam and how to implement it in the context of the production and consumption of fast-fashion clothing.